RELEVANCE OF THE BHAGAVAD GITA'S TEACHINGS TO SPIRITUAL LEADERSHIP AND MODERN BUSINESS ETHICS - Ida Bagus Ngurah (Social Studies and Humanities Journal (SOSHUM), 2025)
The Bhagavad Gita, as one of the sacred texts in Hinduism, not only contains theological and spiritual teachings, but also contains universal values ​​relevant to the challenges of modern life, including in the fields of leadership and business ethics. In the context of globalization and business dynamics filled with competitive pressures, exploring the teachings of the Bhagavad Gita is important to find an ethical and spiritual basis in leadership practices and business decision-making. This study aims to examine the relevance of the teachings of the Bhagavad Gita to spiritual leadership and modern business ethics, by emphasizing the principles of dharma, karma yoga, balance, and moral integrity as universal guidelines.The research method used is library research with a descriptive qualitative approach. Data were obtained through analysis of the primary texts of the Bhagavad Gita, secondary literature in the form of commentaries and academic studies, and previous research from both international and local contexts in Indonesia. The analysis was conducted using a hermeneutic approach to explore philosophical meanings, and a thematic analysis to connect the Gita's teachings with contemporary concepts of spiritual leadership and business ethics.The research findings show that the teachings of the Bhagavad Gita provide a philosophical foundation for service-oriented leadership (seva), sincerity in work without attachment to results (nishkama karma), self-control (samyama), and decision-making based on dharma and universal truth. These values ​​align with the modern spiritual leadership paradigm that emphasizes integrity, self-awareness, and sustainability. Furthermore, in the context of business ethics, the Bhagavad Gita emphasizes the importance of justice, honesty, and social responsibility, which are highly relevant to sustainable business practices. This study confirms that the Bhagavad Gita can be used as a source of inspiration in building spiritual leadership and modern business ethics that are not only oriented towards material gain, but also towards moral, social, and spiritual sustainability.